2015
DOI: 10.1589/jpts.27.1137
|View full text |Cite
|
Sign up to set email alerts
|

Association between mean platelet volume and bone mineral density in patients with ankylosing spondylitis and diagnostic value of diffusion-weighted magnetic resonance imaging

Abstract: [Purpose] The aim this study was to assess the relation between bone mineral density (BMD) and mean platelet volume (MPV) in ankylosing spondylitis (AS) patients, and evaluate the diagnostic role of the diffusion-weighted magnetic resonance imaging (MRI). [Subjects and Methods] Fifty patients diagnosed with AS were divided into two groups on the basis of BMD, a normal group (n=30) and an osteopenic (n=20) group. [Results] Duration of disease in the group with a normal BMD was 10.3±7.0 years, while it was 16.7±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Meanwhile, other previous study reported that PDW and MPV were not correlated with AS activity [21,22]. We assumed that the diverse confounding factors to affect PDW and MPV levels might result in these discrepancies [11][12][13][14][15][16][17][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, other previous study reported that PDW and MPV were not correlated with AS activity [21,22]. We assumed that the diverse confounding factors to affect PDW and MPV levels might result in these discrepancies [11][12][13][14][15][16][17][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies regarding the clinical efficiency of PDW and MPV to reflect AS activity reported inconsistent results, and furthermore, they did not strictly control the confounding factors to affect PDW and MPV [18][19][20][21][22]. In this study, we investigated whether PDW and MPV can reflect disease activity indices of AS in patients without abnormal laboratory results or medical conditions to affect PDW and MPV levels.…”
Section: Introductionmentioning
confidence: 96%
“…Data from Bozan et al, in turn, showed no difference in MPV values of AS patients and healthy controls ( 25 ). In a report where AS patients were stratified in osteopenic or not, MPV values were higher in the former, suggesting a role for MPV in bone loss ( 26 ). Data from Yazici et al showed that MPV was significantly higher in patients with AS than controls; values were reduced by conventional or anti-TNF therapy.…”
Section: Mpv and Rheumatic Diseasesmentioning
confidence: 99%
“…Many studies have shown that the whole blood components including neutrophils, lymphocytes, monocytes, and platelets were correlated with systemic inflammation [8][9][10]. Neutrophil to lymphocyte ratio (NLR), monocyte to lymphocyte ratio (MLR), and platelet to lymphocyte ratio (PLR) have been identified as new inflammatory markers and reported to be higher in axSpA patients and related to disease activity [11][12][13].…”
Section: Introductionmentioning
confidence: 99%